EKONOMI KERAKYATAN VERSUS EKONOMI LIBERAL DALAM PANDANGAN FIQH MUAMALAH - Muheramtohadi, Singgih (Universitas Islam Negeri Sunan Kudus, 2018)
The Debate between neoliberalism thought and populist economic thought is concerned by public attention. The interesting thing on this dcebate is the both of them have the different paradigm and have a big influence in public decision making. This paper discuss what are these paradigms, how it was formaed in the history backgrounds, which the juridical foundations to legalize the thinking, and what the fiqh views. This paper use description and analytical method. The result the discuss, that populist economic thought is closer to islamic view than the neoliberalism though in that he populist thought stands on conscience. And the concscience is one of the fiqh substances, especially concerning about economical relation.